Stickeen man named Charles Barnaby, blacksmith at Fort Simcoe, Washington, 1905. - Meany, Edmond S. (Edmond Stephen), 1862-1935
Man with mustache, dressed in hat, shirt, suspenders, belt, and pants stands outside wooden structure. He wears a Christian cross. In Meany Album v.4, p.20 Caption in album: Charles Barnaby, blacksmith at Fort Simcoe. His father was a Frenchman in the employ of the Hudson Bay Co. His mother was a Stickeen Indian. As a steamboat engineer he was well known among the pioneers of Puget Sound.